The rise of the sidekick: renegotiating the relationship between performance art and performance documentation - Cook, Robyn (My University, 2012)
Within this research project I investigate the uneasy, co-dependent relationship that has developed between performance art and the documentation thereof. ‘Traditional’ performance art1 is understood as a necessarily live medium, one that is available to an audience only through a direct interaction with the artist as ‘performer.’ Documentation as a tangible ‘object’ – be it text, video or photograph – is seen as antithetical to the central position of performance art as a non-material, experiential art form. Despite this dilemma, artists recognise the need to create a record of their performances, both as an archival document, and as a means to distribute it to a wider audience. As such, performance art and performance documentation have slipped into an uneasy hero:sidekick alliance, where documentation is seen only in the role of addendum to the ‘live-act.’ However, a branch of performance art, termed “theatrical performance” has, contentiously, redressed this imbalance (Auslander, 2005: 21). ‘Theatrical’ performance art challenges the core characteristics of ‘traditional’ performance art by presenting a performance to an audience purely as documentation, negating the need for a direct, live encounter with the artist as ‘performer.’ Within this research paper I will argue that the ‘traditional’ relationship between performance art and performance documentation is based on a set of archaic, anti-Modernist, and related anti-commodification, imperatives. I will posit that if these imperatives are removed, ‘traditional’ performance and ‘theatrical’ performance can be commonly seen as sites for creation of “interactivity” (Bourriaud, 2002: 21). As such, it is the inter-human relations represented, prompted or produced by the “artistic proposition” that defines performance art as such, rather than the ‘live-ness’ of the act (Bourriaud, 2002: 21, 33 and Bourriaud in Smith, 2006: 3). This distinction is becoming ever more critical within the current “Digital Age” (Dixon, 2007: 1). Digital transmissions and interactive websites are increasingly challenging the ‘traditional’ hierarchical relationship between the performance act and its representation through documentation (Dixon, 2007: 1). This research project extends across two registers and encompasses both a written and a practical component. Through my research, and a new body of work entitled Girl, you know it’s true, I will mobilise my position on ‘theatrical’ performance as a legitimate species of performance art, a ‘hero’ in its own right.
M.A., Faculty of Humanities, University of the Witwatersrand, 2011